2016
DOI: 10.3389/fnagi.2016.00302
|View full text |Cite
|
Sign up to set email alerts
|

Small Acute Benefits of 4 Weeks Processing Speed Training Games on Processing Speed and Inhibition Performance and Depressive Mood in the Healthy Elderly People: Evidence from a Randomized Control Trial

Abstract: Background: Processing speed training using a 1-year intervention period improves cognitive functions and emotional states of elderly people. Nevertheless, it remains unclear whether short-term processing speed training such as 4 weeks can benefit elderly people. This study was designed to investigate effects of 4 weeks of processing speed training on cognitive functions and emotional states of elderly people.Methods: We used a single-blinded randomized control trial (RCT). Seventy-two older adults were assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 63 publications
2
68
0
Order By: Relevance
“…1. We observed two major weaknesses in the included studies: the assessors are rarely blinded (most of the studies are single-blinded RCT) and the results of only 3 out of the 16 studies [19][20][21] were analyzed in intention-to-treat. In the majority of included studies, the authors recorded drop-out at follow-up and participants did not finish the training session.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. We observed two major weaknesses in the included studies: the assessors are rarely blinded (most of the studies are single-blinded RCT) and the results of only 3 out of the 16 studies [19][20][21] were analyzed in intention-to-treat. In the majority of included studies, the authors recorded drop-out at follow-up and participants did not finish the training session.…”
Section: Resultsmentioning
confidence: 99%
“…For the domain of working memory, 9 studies, with 917 participants, were included [20][21][22][23][24][25][26]29,30 . The forest plot revealed two outlier studies 26,31 that reported extremely large SMD (5.21 [3.62-6.80] and 2.93 [2.54-3.32]).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it has been reported that cognitive activity can modulate subsequent psychological and physiological emotional processes (Iida et al, 2011 , 2012 ). There have also been several studies in which cognitive training for working memory and processing speed reduce negative emotion and depressive symptoms (Takeuchi et al, 2014 ; Nouchi et al, 2016a ). It is important to note that speed of processing involves the parietal and temporal cortices (Turken et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…These cognitive training programs can improve cognitive performance in memory (Mahncke et al, 2006 ; Smith et al, 2009 ), processing speed (Ball et al, 2002 , 2007 ; Edwards et al, 2005 ), executive function (Bissig and Lustig, 2007 ; Uchida and Kawashima, 2008 ), and attention (Mozolic et al, 2011 ) in the healthy elderly population and the elderly dementia population. Cognitive training also improves mental health in older adults (Iida et al, 2011 , 2012 ; Takeuchi et al, 2014 ; Nouchi et al, 2016a ). There are several reasons why we selected SCRA as the intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation